Navigating discrepancies : The assessment of residual lymphovascular invasion in breast carcinoma after neoadjuvant treatment - Kovács, Anikó; Rundgren-Sellei, Åsa; Rask, Gunilla; Bauer, Annette; Bodén, Anna; van Brakel, Johannes; Colón-Cervantes, Eugenia; Ehinger, Anna ; 0000-0001-9225-7396; Hartman, Johan; Acs, Balazs (Breast, 2025)
The assessment of residual lymphovascular invasion (LVI) in breast cancer patients undergoing neoadjuvant therapy may be a critical factor influencing prognosis and treatment decisions. However, there is a notable discrepancy between the RCB, UICC/AJCC, and ICCR guidelines regarding how LVI should be evaluated and reported in this context. ICCR recommends including LVI in the invasive tumor size for neoadjuvant treated patients with only residual LVI affecting the Residual Cancer Burden (RCB) score. AJCC suggests that LVI should not be evaluated as invasive cancer. However, they do not recommend that such cases are considered as complete response. The RCB method does not address the LVI question at all. This editorial aims to explore the implications of these differing recommendations, highlighting the challenges in clinical practice. Even though there is limited evidence in the literature on this subject, leaving this discrepancy unaddressed leads to high variability in the staging of neoadjuvant-treated breast cancer patients among pathologists. This, in turn, may cause confusion in the clinical decision-making for these patients. The recommendation of the Swedish Breast Pathology Expert Group (KVAST breast) based on current evidence, is to report LVI as a separate prognostic biomarker in neoadjuvant setting and reporting it separately from the RCB treatment response criteria. For breast cancer patients with only LVI as residual disease in the breast without any lymph node metastasis after NACT, the Swedish Breast Pathology Expert Group recommends the following staging: RCB-0, pPR, ypT0, ypN0, L1.
Publisher Copyright: © 2025 The Authors
Keywords: Breast cancer staging after neoadjuvant therapy; Lymphovascular invasion; Neoadjuvant therapy; Pathological complete response; Pure intralymphatic breast carcinoma; Residual breast carcinoma; Residual lymphovascular invasion